1986
DOI: 10.1159/000132257
|View full text |Cite
|
Sign up to set email alerts
|

Banded chromosome studies and B chromosomes in wild-caught raccoon dogs, <i>Nyctereutes procyonoides viverrinu</i><i>s</i>

Abstract: Cytogenetic studies were made on Japanese raccoon dogs (Nyctereutes procyonoides viverrinus) that were caught in the wild in southern Kyushu and northern Honshu. G-banding, C-banding, acridine orange (AO) staining following BudR incorporation, and silver staining for nucleolar organizer regions (NORs) were performed on chromosomes from fibroblast cultures. Modal numbers varied from 40 to 42. The karyotype comprised 26 mediocentric and 10 acrocentric autosomes, a submetacentric X, and a minute submetacentric Y.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The localization of the 5S rRNA gene cluster in the Chinese raccoon dog to chromosome 8q1.3 is confirmed by work of Graphodatsky et al (2001), who found canine chromosome 4 to correspond to the long arm of Japanese raccoon dog chromosome 4, which is homologous to Chinese raccoon dog chromosome 8 (Wurster-Hill et al, 1986).…”
Section: Extensive Chromosome Arm Homology In Canidsmentioning
confidence: 65%
See 1 more Smart Citation
“…The localization of the 5S rRNA gene cluster in the Chinese raccoon dog to chromosome 8q1.3 is confirmed by work of Graphodatsky et al (2001), who found canine chromosome 4 to correspond to the long arm of Japanese raccoon dog chromosome 4, which is homologous to Chinese raccoon dog chromosome 8 (Wurster-Hill et al, 1986).…”
Section: Extensive Chromosome Arm Homology In Canidsmentioning
confidence: 65%
“…), published by Mäkinen et al (1985b) was used. For the Chinese raccoon dog (Nyctereutes procyonoides procyonoides) chromosome nomenclature was according to Wurster-Hill et al (1986) and Ward et al (1987).…”
Section: Chromosome Identificationmentioning
confidence: 99%
“…A mechanistically attractive model suggests that B chromosomes represent the small reciprocal products of Robertsonian translocations. Consistent with this hypothesis is the presence of small, monocentric, supernumerary chromosomes in association with Robertsonian chromosomes in humans (Sordo et al, 1983;Abeliovich et al, 1985;Howard and Fielding, 1987) and cattle (Miyake et al, 1994) and the occurrence of B chromosomes in the Robertsonian-derived karyotypes of various rodents and other mammals (Patton, 1977;Volobujev, 1981;Wurster-Hill et al, 1986;Civitelli et al, 1989;Borowik and Engstrom, 1993;Peppers et al, 1997). A second model hypothesizes the origin of B chromosomes as a result of duplication, most likely as polysomy of small autosomes or as isochromosomes of the X chromosome (Patton, 1977).…”
Section: Copyright © 2002 S Karger Ag Baselmentioning
confidence: 92%
“…A second model hypothesizes the origin of B chromosomes as a result of duplication, most likely as polysomy of small autosomes or as isochromosomes of the X chromosome (Patton, 1977). The size similarities between B chromosomes and the smaller A chromosomes within animal karyotypes (e.g., Wurster-Hill et al, 1986;Ś witoń ski et al, 1987;Kolomiets et al, 1988) are consistent with a polysomic origin. Cytogenetic (Blackman, 1988;Fletcher and Hewitt, 1988) and molecular data (Ló pez-Leó n et al, 1994) from various insects support X-chromosome and isochromosome models for the origin of B chromosomes.…”
Section: Copyright © 2002 S Karger Ag Baselmentioning
confidence: 99%
“…The Bs are rather C-band positive; however, the Cbanding patterns are not as distinct as in centromeres of the autosomes. The R-banding showed that these structures are late replicating (WURSTER-HILL et al 1986).…”
Section: Nature Of the B Chromosomesmentioning
confidence: 95%